2022
DOI: 10.3390/plants11030266
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Parameters and Gene Action Associated with Heterosis for Enhancing Yield Characters in Novel Hybrid Rice Parental Lines

Abstract: The technology of hybrid rice utilizing heterosis is an essential requirement for achieving food security. The current study was aimed at assessing the genetic parameters and the gene actions of 15 yield-component traits associated with heterosis, in 9 new parental lines of hybrid rice and their generated hybrids. Five cytoplasmic male sterile (CMS) lines were crossed with four restorer (R) lines using twenty generated line × tester designation hybrid combinations. The results revealed that all the traits were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
(55 reference statements)
7
21
0
Order By: Relevance
“…Furthermore, Anis et al (2019) reported the significance of non-additive gene action in controlling the inheritance of most studied traits. Contrarily, Gaballah et al (2022) reported that the additive variance was the main component of the total genotypic variance. Regarding heritability estimation, in a broad sense (h 2 b%), the results indicated that the heritability values were high for duration, plant height, no.…”
Section: Estimates Of Heterosis Effectsmentioning
confidence: 99%
“…Furthermore, Anis et al (2019) reported the significance of non-additive gene action in controlling the inheritance of most studied traits. Contrarily, Gaballah et al (2022) reported that the additive variance was the main component of the total genotypic variance. Regarding heritability estimation, in a broad sense (h 2 b%), the results indicated that the heritability values were high for duration, plant height, no.…”
Section: Estimates Of Heterosis Effectsmentioning
confidence: 99%
“…erefore, negative heterosis is useful to avoid the tall plant height. Significant negative heterosis for culm length in rice has been reported by Devi et al [36] and Gaballah et al [37]. BM-24 × Gopalbhog (23.55%) and Dehradun pahari × Tulaipanji (19.13%) showed maximum midparent, respectively, for main panicle length.…”
Section: Heterosismentioning
confidence: 62%
“…There are many publications that reported the results of evaluation of gene action and combining ability in very different crops. For example in rice (Ambikabathy et al, 2021;Del Águila & da Silva, 2021;Gaballah et al, 2022), maize (Yu et al, 2020;Coelho, 2021;Sabitha et al, 2021), sweet corn (Khan et al, 2020), cowpea (Owusu et al, 2020), papaya (Vettorazzi et al, 2021), cotton (Giri et al, 2021;Mudhalvan et al, 2021), eggplants (Datta et al, 2021), groundnut (Daudi et al, 2021), common bean (Nkhata et al, 2021).…”
Section: Discussionmentioning
confidence: 99%